"Psychometric properties of the Arabic version of the post-traumatic growth inventory with university students in Jordan. Issue 3 (March 2023) - Al-Nasa'h, Mais; Asner-Self, Kimberly; Al Omari, Hassan; Qashmer, Amani; Alkhawaldeh, Mohammad
Abstract: Post-traumatic Growth plays a key role to cope with traumatic incidents. The scale for Post-Traumatic Growth Inventory (PTGI) has been used by several researchers in different languages. This study aims to evaluate the Arabic-translated version of the PTGI scale by focusing on its validity in different languages and contexts. This study introduces an Arabic version of the PTGI-M normed with 417 undergraduate students at a large university in Jordan. The internal consistency (Cronbach's alpha) and test-retest reliability of the instrument were 0.97 and 0.82, respectively. Bivariate correlation was used to approximate the concurrent validity (CV). Significant correlations were found between the PTGI-M and the beck depression inventory (BDI), perceived stress scale (PSS), Taylor's manifest anxiety (TMAS), satisfaction with life (SWL), and the Rosenberg self-esteem scale (RSES). Confirmatory factor analysis (CFA) to assess the convergent and discriminant validity of the translated scale. Convergent and discriminant validity was established for the Arabic version of the PTGI-M by conducting a confirmatory factor analysis (CFA). In conclusion, this study proposes that future investigations should consider analysing the total PTGI-M subtotal scores to comprehend the complexity of the post-traumatic growth experience.